Музейна справа у формуванні регіональної ідентичності населення (на прикладі Природничо-історичного музею Полтавського губернського земства) - Белько, О.О. (Сіверщина в історії України, 2022)
Стаття присвячена ролі музейних закладів у формуванні регіональної ідентичності населення на прикладі діяльності Природничо-історичного музею Полтавського губернського земства. Регіональна ідентичність, регіональне самовизначення, самосвідомість є важливими факторами функціонування місцевості як єдиного територіального і соціокультурного простору. У статті розкрито особливості краєзнавчої роботи закладу. Наведено приклади заходів, які проводилися на терені Полтавщини, зокрема, відкриття Центру досліджень кустарної справи, де на науковому ґрунті вивчалися традиційні і нові кустарні промисли Полтавщини. Наводяться приклади, як, проводячи різнопланову роботу зі збереження історії та культури, традицій та ремесел області, музейний заклад не лише підтримував регіональну унікальність, а й створював сталий образ місцевості, що і на сучасному етапі слугує опорою для зародження регіональної самосвідомості. The article is devoted to the role of museum institutions in the formation of regional identity of the population on the example of the Natural History Museum of Poltava Provincial Zemstvo. Regional identity, regional self-determination, self-awareness are important factors in the functioning of the area as a single territorial and socio-cultural space. The article reveals the peculiarities of the local lore work of the institution. Examples of events held in Poltava region are given, in particular, the opening of the Center for Handicraft Research, where traditional and new handicrafts of Poltava region were studied on a scientific basis. Ethnographic local lore was considered as one of the defining aspects of the study of the history and traditions of the region, the formation of regional identity. Characteristic features of studying a specific material rooted in the archaic layers of folk traditional culture in the creation of expositions of contemporary museum institutions are given. After all, over the centuries the nature of the expositions of the Vasyl Krychevsky Poltava Museum of Local Lore gradually transformed - from the typological grouping of museum objects at the beginning of the last century, through the ensemble method of display over time to the creation of architectural and artistic images in the new Ukrainian renaissance. Examples are given of how the institution not only maintained regional uniqueness, but also created a sustainable image of the area, conducting various activities to preserve the history and culture, traditions and crafts of the region, which at the present stage serves as a support for the emergence of regional identity. After all, it is the regional museum institutions focused on the preservation of characteristic features important for the spiritual development of the population, namely the history and culture of the area, its ethnic composition.